Rekomendasi Peralatan Camping Menggunakan Metode Complex Proportional Assesment - Naufal, Mohammad Farid; Prasetyo, Daniel Hary; Ramadhan, Firman Herda (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Boss camping is a company engaged in services, namely the rental of camping equipment. Because it is engaged in goods rental services, the company uses a social media operating system to carry out its operational activities. The system is expected to make it easier to rent and provide real-time equipment information so that customers do not need to go to the rental place to check the stock of equipment to be borrowed, so as to make it easier for customers who will rent climbing equipment. In addition, this system is able to assist admins in managing data, so as to provide valid and accurate information. The decision support system was obtained using the Copras (Complex Proportional Assessment) method. The Copras method is applied in a decision support system in order to solve the problem because it is used to calculate the utility of a predetermined alternative for comparison and calculate the evaluation of the maximum and minimum criteria separately